2008
DOI: 10.1089/aid.2007.0215
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Strongly Activating Human Anti-CD40 Antibody That Suppresses HIV Type 1 Infection

Abstract: We characterized the functional properties of a novel set of human anti-CD40 monoclonal antibodies originating from a human phage display library and identified an antibody that strongly activates cells via the CD40 receptor for potential use in HIV therapy. The anti-CD40 antibodies were converted from a single chain antibody fragment format (scFv) to an IgG format and produced in HEK293 cells, and the binding characteristics were evaluated. Next, their ability to (1) rescue a human B cell line from induced ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…23) and B44 (19) were produced by transient expression in HEK cells and subsequent purification on protein A columns. An aglycosylated variant of ADC-1013, referred to as ADC-1013-N297Q, was produced by introducing a single N297Q mutation in the Fc-region.…”
Section: Antibodies and Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…23) and B44 (19) were produced by transient expression in HEK cells and subsequent purification on protein A columns. An aglycosylated variant of ADC-1013, referred to as ADC-1013-N297Q, was produced by introducing a single N297Q mutation in the Fc-region.…”
Section: Antibodies and Cell Linesmentioning
confidence: 99%
“…To translate these findings into the clinic, we set out to engineer a CD40 agonistic antibody (18,19), ADC-1013, using Fragment INduced Diversity (FIND; ref. 20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to targeting host receptors, a few studies reported the identification of peptides or antibody fragments directed against other host proteins such as cell surface determinants (CD) or intracellular enzymes [188,190,195,196]. The CD40 receptor, a member of the tumor necrosis factor receptor superfamily, and its CD40L ligand are involved in several biological processes including cell proliferation, activation and production of cytokines and chemokines.…”
Section: Identification Of Hiv-1 Inhibitors By Phage Displaymentioning
confidence: 99%
“…In 2002, Ellmark et al identified a set of anti-CD40 antibody fragments through biopanning of a human ScFv phage library against a biotinylated CD40 antigen [189]. When expressed as full-length IgG1 one antibody (clone B44) suppressed HIV-1 infection by a R5-tropic virus, most probably through induction of CC chemokine production [188]. More recently, the DDX3 protein, a cellular RNA helicase involved in RNA unwinding was shown to play important roles in HIV-1 replication.…”
Section: Identification Of Hiv-1 Inhibitors By Phage Displaymentioning
confidence: 99%